Successful treatment of extensive-stage small cell lung cancer with concurrent pleural and pericardial effusions: Case report - Kashima, Ayaka; Fukuda, Yosuke; Shimamura, Miri; Ijichi, Miharu; Sagara, Hironori (Frontiers in Oncology, 2022)
There is no evidence whether pleural/pericardial drainage and pleurodesis/pericardiodesis should be performed first or chemotherapy should be initiated first for chemotherapy-sensitive small-cell lung cancer. A 76-year-old woman presented to the emergency department with progressive dyspnea on exertion for a week. Chest computed tomography showed a mass shadow ventral to the left upper lobe, bilateral pleural effusions, and pericardial effusion circumferentially around the entire pericardium. We diagnosed extensive-disease small-cell lung cancer based on the clinical course and pathological findings. We first performed pleurodesis and pericardial drainage and successfully initiated immune checkpoint inhibitor combined chemotherapy with improved performance status. This case highlights the importance that aggressive drainage and pleurodesis/pericardiodesis should be considered before systemic chemotherapy in coexisting pericardial or pleural effusions, even in patients with small-cell lung cancer who are sensitive to chemotherapy.